Self-healing and cell adhesion properties of dynamic and photo-crosslinking PEG-based dual networks soft hydrogels - OKTAY, BURCU (My University, 2024)
Self-healing involves an autonomic response that repairs damage to living systems. In this study, polyethylene glycol (PEG) underwent aldehyde-functionalization using the Albrigh Goldman oxidation technique. Flexible, dynamic crosslink points to encourage self-healing are generated by the formation of acylhydrazone bonds formed between long-chain PEG dialdehyde and adipic acid dihydrazide. Furthermore, methacrylated PEG was synthesized to support the polymer matrix through dynamic covalent bonds. The hydrogels exhibited self-healing within the first 4 hours at room temperature and after 24 h. hydrogels with mechanical performance close to the original were obtained. They have good tensile and elongation strength and are well-suited for interaction with living cells.
Keywords: Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; POLİMER BİLİMİ; KİMYA, FİZİKSEL; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; POLYMER SCIENCE; CHEMISTRY, PHYSICAL; MATERIALS SCIENCE, MULTIDISCIPLINARY; Fiziksel ve Teorik Kimya; Fizik Bilimleri; Polimerler ve Plastikler; Malzeme Kimyası; Physical and Theoretical Chemistry; Physical Sciences; Polymers and Plastics; Materials Chemistry; dynamic covalent bonding; self-healing; soft hydrogels